A stochastic dynamic programming technique for property market timing - Tao, Yong Hua. (2008)
The aim of this dissertation is to investigate whether the property market timing model developed using the stochastic dynamic programming approach provides superior return over the buy-and-hold and naive timing strategies. In this dissertation, the naive timing strategy is designed with the assumption of perfect information on the market movement.